Analysis of the Effect of Tax Policy and Inflation on Economic Growth: A Review of Indonesian Literature - Nur Sandi Marsuni; Mutahira Nur Insirat (GoodWill, 2023)
This study examines the impact of tax policy and inflation rates on Gross Domestic Product (GDP) in Indonesia through a literature review approach. Tax policy and inflation are crucial determinants of economic growth as they affect government revenue and consumer purchasing power, respectively. The qualitative method used in this research synthesizes findings from various scholarly articles, books, and reports to analyze the relationship between tax policy, inflation, and GDP growth. The findings reveal a positive correlation between tax revenues and GDP growth, suggesting that higher tax rates can stimulate economic activity through increased public spending on infrastructure and social programs. Similarly, inflation, when controlled within moderate levels, can positively influence GDP by enhancing consumer spending and business investment. This study contributes to the theoretical and empirical understanding of economic growth determinants in Indonesia, providing valuable insights for policymakers to formulate effective economic strategies.